2023
DOI: 10.1002/jimd.12676
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin precursors and risk of primary liver cancer in acute intermittent porphyria: A case–control study of 188 patients

Mattias Lissing,
Axel Wester,
Daphne Vassiliou
et al.

Abstract: Acute intermittent porphyria (AIP) is a rare hereditary metabolic disease characterized by acute attacks and accumulation of the porphyrin precursors 5‐aminolevulinic acid (ALA) and porphobilinogen (PBG). Patients with AIP have a high risk of primary liver cancer (PLC). We aimed to assess the association between porphyrin precursor excretion and the risk for PLC in patients with AIP. We studied 48 patients with AIP who developed PLC between 1987 ‐ 2015 and 140 age and sex matched controls with AIP but no PLC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…Several studies have found a connection between porphyria and other diseases [ 13 15 ]. In fact, a possible association between AIP and liver cancer was identified in a cohort study through investigation on porphyria biomarkers [ 16 ]. In another cohort study comprising patients with AIP, researchers confirmed a high risk of primary liver cancer and identified a strong association with AIP biomarkers [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found a connection between porphyria and other diseases [ 13 15 ]. In fact, a possible association between AIP and liver cancer was identified in a cohort study through investigation on porphyria biomarkers [ 16 ]. In another cohort study comprising patients with AIP, researchers confirmed a high risk of primary liver cancer and identified a strong association with AIP biomarkers [ 17 ].…”
Section: Introductionmentioning
confidence: 99%